AKTIVITAS PEMBELAJARAN DARING SISWA MADRASAH IBTIDAIYAH DI MASA PANDEMI COVID-19 DESA NANGGERANG KECAMATAN CILILIN KABUPATEN BANDUNG BARAT - Hevie Setia Gunawan (LPPM STAI Darul Falah, 2022)
The prolonger covid-19 pandemic has hit countries around he world, including Indonesia, face to face learning activities in schools are now being replaced by online learning.Several problems arise, including: parents have difficult in providng learning assistance, do not understand explaining to children about the material and assignments given by the teacher also the level of student desre online learning is very low. Online learning mentoring activities are community service programs, the goal is to be able to help parents who have difficulties in providing learning assistance also help students to have a high desire to learn online. The parties involved are RT and RW, Karangtaruna, teachers, village officials, parents and the community. This learning mentoring activity involved KKN students from STAI Darul Falah. The method used is independent KKN assistance. The stages of learning mentoring include program planning, program implementation and evaluation.the results found in the field, this community service activity is very much needed and provide great benefits especially for parents and students,parents feel helped by the presence of learning companions for thir children, also the enthusiasm of students in learning is getting higher and is expected to have a good impact on learning outcomes at school, so that community service activities like this are very important to cary out.